Design and fabrication transparent trolley toolbox - Mohd Firdaus, Ahmad Sani (2007)
This project is about designing and fabricating the toolbox that can store and keep the laboratory equipment. It also has portability and easy to see from outside of the toolbox. Another purposes this toolbox give the user the easy to see inside the toolbox with more directly. Numerous methods and process involve in this project for instance joining using welding process. The process to cut the sheet metal follows on their required dimension by using Turret Punch Machine. Besides that, the cutting laser Machine was use to cut the prospect. After all the process had been done, this Transparent Trolley Toolbox project will help us to understand the fabrication and designing process that involved in this project.